Taxanes‐induced cutaneous eruption: another histopathologic mimicker of malignancy. (11th November 2015) - Prieto‐Torres, L.; Llamas‐Velasco, M.; Machan, S.; Haro, R.; de Asis, S.; Carmo, M.; Loredo, A.; del Puerto, C.; Fried, I.; Kempf, W.; Cerroni, L.; Requena, L.
Abstract: Background: Paclitaxel and docetaxel are antineoplastic drugs that bind the microtubules, producing the arrest of mitoses, which may be seen histopathologically. These histopathologic changes may simulate an intraepidermal keratinocytic malignant neoplasm, and an accurate diagnosis may be only established by clinicopathological correlation. Objectives: We report six cases of cutaneous eruptions by taxanes in which a striking cytotoxic effect was evident histopathologically. Methods: Cutaneous biopsies were obtained in each patient. Results: Atypical starburst‐like or ring‐like mitoses and dyskeratosis on basal and suprabasal layers of the epidermis. Areas of squamous syringometaplasia were also seen in one case. Discussion: These findings were interpreted as expression of mitotic arrest due to taxanes. Similar changes have been described in association with other chemotherapeutic drugs such as vincristine, podophyllin and its derivative etoposide; colchicine, busulfan and maytansine, but cases like ours due to taxanes are exceptional or under‐reported. Conclusion: Dermatopathologists should be aware of these effects in order to interpret carefully cutaneous biopsy specimens of patients receiving taxanes.